Zinc distribution in structural components of high kernel‑zinc maize and its retention after milling - Taleon, Victor; Palacios-Rojas, Natalia; Dollah, Yusuf; Rosales, Aldo; Kalejaiye, Olatundun; Menkir, Abebe (Elsevier, 2025)
High kernel‑zinc maize (HKZM) has the potential to contribute to addressing zinc deficiency in regions with high maize consumption, particularly in Sub-Saharan Africa. However, milling HKZM may lead to loss of zinc when removing the pericarp and embryo. This study evaluated the zinc distribution in kernel components of HKZM maize grown in different environments, and examined how milling affected its zinc concentration. The zinc concentration in HKZM lines was 27.0–30.7 μg g−1 while in conventional maize it was 19.5–22.6 μg g−1. Zinc in maize endosperm represented 20.5 to 28.2 % of the total kernel zinc while that in the embryo represented 68.1 to 75.7 %. HKZM retained 43 % of its kernel zinc after milling, resulting in flour with 5 μg g−1 higher zinc concentration compared to regular maize flour. Environmental factors had a significant effect on kernel zinc concentrations. Maize grain from commercial mills had 21 μg g−1 zinc, with zinc losses of 22 % to 65 % during milling, resulting in flours with 6–10 μg g−1 of zinc. While HKZM shows promise in alleviating zinc deficiency, its anticipated impact may be limited in regions where refined maize is frequently used for making foods. The development of maize varieties with higher zinc concentration in the endosperm, along with promoting increased consumption of less refined maize products can boost zinc intake for deficient populations.